2017
DOI: 10.1158/1541-7786.mcr-17-0293
|View full text |Cite
|
Sign up to set email alerts
|

NAD Synthesis Pathway Interference Is a Viable Therapeutic Strategy for Chondrosarcoma

Abstract: Nicotinamide phosphoribosyltransferase (NAMPT) and nicotinic acid phosphoribosyltransferase (NAPRT) are rate-limiting enzymes in the NAD synthesis pathway. Chondrosarcoma is a malignant cartilage forming bone tumor, in which mutations altering isocitrate dehydrogenase-1 and -2 (IDH1 and IDH2) activity have been identified as potential driver mutations. Vulnerability for NAD depletion has been reported for -mutant cells. Here, the potency of NAMPT inhibitors as a treatment of chondrosarcoma was explored. Eleven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 38 publications
4
36
1
Order By: Relevance
“…In vitro studies have shown promising results using a NAMPT inhibitor in cancer cells, especially the IDH1/2 mutant cancer cell lines (Table 1). MGG119, MGG152, BT142 primary glioblastoma cell lines; HT1080, 30T and SW1353 chondrosarcoma cell lines; SNU484, SNU668, SNU1750, MKN1 and Hs746T gastric cancer cell lines which have mutations in IDH1 [7][8][9], were sensitive to NAMPT inhibition. NAMPT inhibitors not only have shown promising effect as single-agent therapy, but were also found to sensitize other modalities of cancer treatment in both in vitro and in vivo experiments [45,[55][56][57], as shown in Tables 2 and 3.…”
Section: Therapeutic Role Of Nampt In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro studies have shown promising results using a NAMPT inhibitor in cancer cells, especially the IDH1/2 mutant cancer cell lines (Table 1). MGG119, MGG152, BT142 primary glioblastoma cell lines; HT1080, 30T and SW1353 chondrosarcoma cell lines; SNU484, SNU668, SNU1750, MKN1 and Hs746T gastric cancer cell lines which have mutations in IDH1 [7][8][9], were sensitive to NAMPT inhibition. NAMPT inhibitors not only have shown promising effect as single-agent therapy, but were also found to sensitize other modalities of cancer treatment in both in vitro and in vivo experiments [45,[55][56][57], as shown in Tables 2 and 3.…”
Section: Therapeutic Role Of Nampt In Cancermentioning
confidence: 99%
“…IDH mutations have been associated with several cancers, in particular, WHO grade II/III and secondary glioblastoma multiforme (GBM), acute myeloid leukemia (AML), intrahepatic cholangiocarcinoma, gastric cancer and cartilaginous tumors [9,[82][83][84][85]. Most of mutant IDH1 tumors have a single, missense mutation at codon 132 that changes arginine to histidine (IDH1 R132H ).…”
Section: Mutant Isocitrate Dehydrogenases Inhibit Nad Production In Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Glutaminolysis and NAD synthesis pathways are potentially other vulnerable targets in the context of IDH mutated chondrosarcomas, but their clinical applications remain to be determined [46,47].…”
Section: Current Therapeutic Approaches In Chondrosarcomamentioning
confidence: 99%